The perception of COVID-19 and avoidance behavior in Turkey: the role of income level, gender and education - Abdulmuhsin, Amir A.; Degirmenci, Bekir; Efendioglu, Ibrahim Halil; Durmaz, Yakup (EMERALD GROUP PUBLISHING LTD)
Purpose This study aims to reveal both the effect of the perception of COVID-19 on avoidance behaviors and the mediating role of the perception of personal control in this relationship. COVID-19 emerged in December 2019 and since then, it has spread globally in a short period and has affected people socially, economically and culturally. Design/methodology/approach The data for the research was collected from 418 participants during COVID-19, through online questionnaires. The obtained data were analyzed through AMOS and SPSS software using structural equation modeling. Findings The research results show that some perceptions of COVID-19 affect avoidance behavior and that personal control has a mediating role. It has also been found that gender plays a moderating role in the relationship between COVID-19 and avoidance behavior. It has been found that women are especially more sensitive compared to men in perceiving COVID-19. This study also found that perception of COVID-19 changes depending on income. Practical implications After the pandemic is over, people will get in contact with each other less than before, and trade will change accordingly. People will avoid shopping in crowded places, and consumer behaviors will undergo different changes. All of these results considered, it is expected that avoidance behavior will cause some permanent behavioral changes in consumers. Originality/value The study answers the critical question about the effect of the perception of COVID-19 on avoidance behavior. Furthermore, the role of income level, gender and education in this relationship will be highlighted.
Keywords: COVID-19; Lay theory; Avoidance behavior; Consumer behavior; Turkey; Emerging markets